STUDY AND DESIGN OF A PROTOTYPE THAT ALLOWS TO CONTROL THE LOAD OF URBAN PUBLIC TRANSPORT TO RECORD THE EXCESS OF CAPACITY IN THE UNIT - Moyón Gusqui, Juan; Moreno Pallares, Rodrigo; Aguilar Miranda, Gustavo (mktDESCUBRE; Vol 1 No 2 (2020): Special Edition 3rd International Scientific Congress of Administrative and Financial Sciences FADE 2019DO - 10.36779/mktdescubre/v#.#, 2020)
The following project specific the design and construction of an electronic prototype that allows measurement of the displacement of the suspension of an urban passenger bus, for which the design in SolidWorks of the chassis. The bodywork and power train were executed based on the INEN 1323 technical standard, on the other hand, to find the deformation of the leaf spring with respect to the chassis, the finite element method was used, considering all the factors that intervene in the deformation of the suspension is to say the maximum permissiblecdead loads, finally it build an electronic device using a laser distance sensor, in addition, a global position system that will allow knowing the exact location of the unity. The implemented system generates a pair of data every second depending on the date, time, geographical location, speed and excess load, when there is a value outside the driving range a signal of the violation will be sent and a link with the exact coordinates executable with Google Maps, therefore It has a reliable system of alert and data collection driving cycle of the unit for a later analysis.